1999
DOI: 10.1211/0022357991776903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-diabetic Property of Morinda lucida Leaves in Streptozotocin-diabetic Rats

Abstract: The hypoglycaemic and anti-hyperglycaemic activities of a methanol extract of Morinda lucida Benth. (Rubiaceae) leaves were studied in normal and streptozotocin-diabetic rats. In normal rats, the extract demonstrated a significant (P < 0.05) and dose-dependent hypoglycaemic activity within 4 h after oral administration. The plasma glucose level of 400 mg kg(-1) of the extract at 4 h was 42.5 +/- 0.4 mg/100 mL (control 67.4 +/- 1.2 mg/100 mL). After 12 h, the plasma glucose level of rats administered 50, 100, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Result of this study is in consonance with that reported for the dried leaves extract of Morinda lucida Benth. in normal and streptozotocin diabetic rats, by Olajide et al (1999). Equally, Olajide et al (1999) and Asuzu and Chineme (1990) independently reported Morinda leaves to contain high concentrations of flavonoids, alkaloids, tannins and saponin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Result of this study is in consonance with that reported for the dried leaves extract of Morinda lucida Benth. in normal and streptozotocin diabetic rats, by Olajide et al (1999). Equally, Olajide et al (1999) and Asuzu and Chineme (1990) independently reported Morinda leaves to contain high concentrations of flavonoids, alkaloids, tannins and saponin.…”
Section: Discussionmentioning
confidence: 97%
“…in normal and streptozotocin diabetic rats, by Olajide et al (1999). Equally, Olajide et al (1999) and Asuzu and Chineme (1990) independently reported Morinda leaves to contain high concentrations of flavonoids, alkaloids, tannins and saponin. Literature has equally shown the biological activities of alkaloids and flavonoids to include hypoglycemia, hypolipidemia, hypoazotemia, hypotension among other biological effects (Oladele et al, 1995;Sudheesh et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…For ages, many countries have applied traditional medical plants to treat hyperglycemia and diabetes mellitus [1,6,13,26], and more than 400 plants have been reported with their glucose reduction effects [2]. Recently the interest on medical plants is getting high as oral agents used to treat DM cause various side effects [4,15] while taking traditional medical plants in a natural form of extracts show treatment effect as good as that of therapeutic agents without side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia triggered by DM is usually caused due to the decrease in insulin secretion, decrease in glucose utilization of tissue and increase in the generation of glucose. Hyperglycemia's symptoms include obsessive thirst, glucosuria, polyuria, lipemia and hunger, and if left without treatment, this can result in patient's death due to critical ketoacidosis [27].For ages, many countries have applied traditional medical plants to treat hyperglycemia and diabetes mellitus [1,6,13,26], and more than 400 plants have been reported with their glucose reduction effects [2]. Recently the interest on medical plants is getting high as oral agents used to treat DM cause various side effects [4,15] while taking traditional medical plants in a natural form of extracts show treatment effect as good as that of therapeutic agents without side effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation